2016
DOI: 10.1128/jvi.02694-15
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Flux Is Required for Endosomal Progression of African Swine Fever Virions during the Initial Establishment of Infection

Abstract: African swine fever virus (ASFV) is a major threat for porcine production that has been slowly spreading in Eastern Europe since its first appearance in the Caucasus in 2007. ASFV enters the cell by endocytosis and gains access to the cytosol to start replication from late endosomes and multivesicular bodies. Cholesterol associated with low-density lipoproteins entering the cell by endocytosis also follows a trafficking pathway similar to that of ASFV. Here we show that cholesterol plays an essential role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…A collapse of endosomes to the perinuclear area is also a characteristic phenotype of an alteration of endosomal cholesterol efflux [ 26 ]. Also, recent publications from our laboratory demonstrated that accumulation of cholesterol in endosomes caused by a chemical inhibition of cholesterol flux, causes virion retention inside endosomes and inhibition of infection progression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A collapse of endosomes to the perinuclear area is also a characteristic phenotype of an alteration of endosomal cholesterol efflux [ 26 ]. Also, recent publications from our laboratory demonstrated that accumulation of cholesterol in endosomes caused by a chemical inhibition of cholesterol flux, causes virion retention inside endosomes and inhibition of infection progression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have described accumulation of cholesterol upon overexpression of IFITM2 and IFITM3. We have recently reported that inhibition of cholesterol exit from endosomes using chemical inhibitors causes retention of virions inside these vesicles, thus impairing progression of the infection [ 37 ]. Altogether these data could suggest that the antiviral action of IFITMs may affect to a higher extent to those viruses that require the endosomal pathway during the early stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The acidic environment of late endosomes is necessary for the virus to loss its capsid and acidification inhibitors such as Bafilomycin inhibit decapsidation and further infectivity. Also, alterations of cholesterol transport inhibit virion fusion and progression along the endocytic pathway [ 27 ]. After fusion of viral internal membrane with the viral membrane, naked cores are released to the cytoplasm to start replication [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In macrophages, miR-10b is known to target ATP binding cassette transporter A1 ABCA1 ( 45 ), which is involved in the regulation of cholesterol efflux. During infection with ASFV, cholesterol remodeling is essential in the establishment of productive viral infection, and disruption of cellular cholesterol efflux leads to the impairment of virus entry and viral particles remained trapped in endosomes ( 46 ). This suggests a link between miR-10b, ABCA1, and cholesterol efflux during endocyte-mediated entry of ASFV in macrophages.…”
Section: Discussionmentioning
confidence: 99%